Legislative framework of cannabis within the European Union. Analysis of legal status of recreational cannabis for personal possession - Mirošņičenko, Aļona (Riga Graduate School of Law, 2019)
This study reflect current legal situation in the European Union regarding legislation of cannabis. Taking into account the increasing tendency of this topic, the analysis is based on the assumption that cannabis although usually perceived as a soft drug, is a transnational threat as every narcotic substance. Therefore, it is necessary to analyze and work on this matter to ensure that fundamental values of human life are not negatively affected by the growing trend of liberalization of cannabis. The focus is on the recreational cannabis for personal possession as this type of usage is referred in the statistical data of countries most often. This study is not dealing with the medical cannabis and related to it issues. The work focuses mainly on the personal possession of recreational cannabis and evaluates its legal status in European Union Member states. Research is focusing more on Portugal, Spain, France and Netherlands. The main objective of this study is to illustrate the existing current grey area in law and explain its effects on states from the legal, social and economic point of view. Two research questions of this work contribute to the better understanding of the subject matter of this thesis. Research question are as follows: 1. How the European Union law harmonizes the legislation of recreational cannabis for personal possession and protection of public health? 2. Is the decriminalization of possession of recreational cannabis for personal use consistent with EU and International Drug Law? Research provides variety of statistical data gained from official national drug addiction agencies. Reports from independent agencies are used in this work as well. The results of research highlighted the existing loophole in the law. Primarily, in the International Drug law, as this law is a core for the whole European Union and member states consequently.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Cannabis